To Compare Prophylactic Zinc Supplementation Versus Placebo in Terms of Frequency of Diarrhea in Infants of 6-11 Months (Medical Forum Monthly, 2024)
Objective: To compare prophylactic zinc supplementation versus placebo in terms of frequency of diarrhea in infants of 6-11 months.Study Design: Randomized control trial studyPlace and Duration of Study: This study was conducted at the Outpatient Department of Pediatrics, POF Hospital, Wah Cantt from March 2016 to September 2016.Materials and Methods: Non Probability Consecutive sampling was used to enroll children and was divided into two groups by lottery method as control group receiving placebo and case group receiving the supplemental zinc. The case group was then given 5ml of syrup containing 20 mg of elemental zinc daily for 2 weeks followed by 6 months of follow-up. The control group was given placebo. At each follow-up, the mother/caregiver was asked about the occurrence of diarrheal episodes and duration of diarrhea during the previous month.Results: Total of 120 children were included in the study and divided into two equal groups. In group A (control group) mean age 8.23 months and SD +1.37. In group B(case group) mean age 8.02 months and SD +1.17. In group A minimum diarrhea episode was nil, maximum diarrhea episodes were 15 with mean diarrhea episodes 8.53 and SD +3.15. In group B minimum diarrhea episode was nil, maximum were 9 with mean diarrhea episodes 5.13 and SD +2.73.Conclusion: Diarrhea is a common disease in developing countries with significant morbidity and mortality. Results of the current study show significant reduction in diarrheal morbidity in infants even 6 months after short-course of zinc prophylaxis.